THE SYSTEM OF UNIVERSITIES' ACADEMIC STAFF VALUES: METHODOLOGICAL ASPECT - Iryna Reheilo (National Academy of Educational Sciences of Ukraine, 2018)
The purpose of the study is to find out the methodological foundations of the system of values of universities' academic staff in the scientific achievements of domestic researchers. The legislative documents, which ratified the system of national values in general and values in the field of education in particular, are analyzed. It was discovered that the transformation of values is taking place, such as national values - national interests - national goals. The role of values in the educational process is revealed, their significance is established among the rights and responsibilities of participants in the educational process. The theoretical views of researchers are investigated and general approaches to studying the problem of values in the branches of philosophy, sociology, psychology, pedagogy are generalized. It was found out that the system-forming core of the personality are values (value orientations) that become relevant not only as the dominant direction of research in higher education in general, but also as a result of learning within the framework of obtaining value competences. It is substantiated that in the research of values (value orientations) of academic staff, it is expedient to use such methodological approaches: interdisciplinary, systemic, competence, activity, personality-oriented, cultural, axiological, social, synergetic and acmeological. The basic principles of values (value orientations) of universities' academic staff are developed, which will promote effective its selection: professionalism, moral and ethics, responsibility, impartiality, trust, success, priority, identification.